Enhancing Questioning Skills in Preschool Children with Speech Delays Through Project-Based Learning - Nursari, Amelia; Sukinah, Sukinah (Journal of Innovation and Research in Primary Education, 2025)
Speech delays affect 5-10% of preschool children and significantly impact questioning skill development, which is essential for cognitive growth and academic success. This study investigated the effectiveness of project-based learning in enhancing questioning competencies among kindergarten children with speech delays. A classroom action research design following Kemmis and McTaggart's spiral model was implemented across three intervention cycles with two kindergarten students (aged 4-6 years) diagnosed with speech delays in East Kalimantan, Indonesia. Data collection employed structured observation rubrics assessing questioning behaviors across four dimensions: question initiation frequency, complexity, contextual appropriateness, and verbal clarity. Project-based learning activities focused on environmental exploration and geometric shape identification through collaborative maket construction. Quantitative analysis examined pre-post score comparisons, while qualitative data underwent thematic analysis with triangulation across multiple sources.  Participants demonstrated substantial improvement in questioning skills, with overall mean scores progressing from 1.55 (baseline) to 3.24 (post-intervention), representing a 109% increase. The most significant improvements occurred in question type diversity (275% increase), question quality (200% increase), and independence in question formulation (216.7% increase). Performance classifications advanced from "beginning to develop" to "developing very well" across all measured competency areas. Both participants achieved age-appropriate questioning competencies by intervention completion. Project-based learning methodology effectively enhanced questioning skills among children with speech delays through authentic learning contexts that stimulated natural inquiry behaviors. The findings support constructivist and experiential learning theories while demonstrating the potential of inclusive pedagogical approaches. These results have significant implications for early childhood education practices, suggesting that strength-based interventions can successfully address communication challenges while promoting collaborative learning and cognitive development.